Influence of Food Quality, Hygiene, and Price on Word-of-Mouth: A Case Study of Local Restaurants in Surat Thani Province, Thailand - Siripat Chodchuang; Kitiya Made; Kanyanat Nujinjit; Banthita Samosorn; Parichamon Waiprib; Pattamawan Sanjorn; Phanutchanat Phetchamnan; Suchawan Suwannao (AMAR (Andalas Management Review))
This research aims to study the influence of quality, hygiene, and price factors on word-of-mouth: A case study of local restaurants in Surat Thani Province. Data were collected through questionnaires from consumers who dined at the restaurants, totaling 400 sets, using non-probability convenience sampling method. The statistics employed were descriptive statistics including percentage, mean, and standard deviation, and inferential statistics including multiple linear regression analysis. The research findings revealed that food quality influence, hygiene influence, and price influence significantly affected consumers' word-of-mouth in the case study of local restaurants in Surat Thani Province at the 0.05 statistical significance level. The hierarchical order of variable influence from highest to lowest was: price influence (β = 0.34), followed by hygiene influence (β = 0.26), and food quality influence (β = 0.17). Therefore, local restaurant operators should prioritize serving food at appropriate temperatures, maintaining clean surrounding environments with proper ventilation, and setting reasonable prices when compared to food portions to ensure consumers perceive value for money, leading to satisfaction and word-of-mouth recommendations.